Insects in a warming world: responses and challenges - Ravuri, Prasanna lakshmi; Mandali, Rajasri; Deva, Sahaja; Reddy, P Karthik (Indian Journal of Plant Protection, 2025)
Global climate change, driven by rising greenhouse gas emissions, significantly impacts agro-ecosystems. Atmospheric CO₂ levels have risen sharply from 280 ppm to 420 ppm and may double by 2100. Over the past century, the global average temperature has increased by 0.8°C and is projected to rise further, triggering widespread changes in the biosphere. These environmental shifts influence insect pest dynamics. Higher CO₂ levels enhance plant photosynthesis, increasing the carbon-to-nitrogen (C:N) ratio in leaves. This reduces leaf nutritional quality, causing slower insect development, lower reproduction, and higher mortality. Consequently, natural enemies feeding on these insects may also be affected. Temperature plays a crucial role in insect behaviour, development, and distribution. Rising temperatures can alter pest population size (increase or decrease), shift insect geographic ranges and modify life cycle timing and overwintering behaviour. A 2°C temperature rise could allow insects to complete 1-5 extra generations per season. Climate warming also disrupts interactions between species across trophic levels. To manage insect pests effectively under changing climate conditions, strategies must include continuous monitoring and surveillance, international collaboration and data sharing and development of adaptive and sustainable pest management approaches.